2016
DOI: 10.3892/mco.2016.1101
|View full text |Cite
|
Sign up to set email alerts
|

An increased neutrophil-to-lymphocyte ratio predicts poorer survival following recurrence for patients with breast cancer

Abstract: The aim of the present study was to evaluate the association between changes in the neutrophil-to-lymphocyte ratio and the survival rate, as well as tumor subtype, in recurrent breast cancer. Patients with recurrent breast cancer following surgery were included in this study. NLR was calculated and compared between two time points: Pre-treatment and recurrence. The associations between the longitudinal NLR change, the NLR at the time of recurrence and overall survival following recurrence (OSrec) were evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 22 publications
4
50
0
Order By: Relevance
“…Interestingly, we found only one study comparing NLR measurements between two different time points: pretreatment and at recurrence. The study by Iwase et al [23] found an increase in NLR by an average of 0.59 at recurrence compared to the initial measurement in a small study on patients with recurrent breast cancer. It was also reported that TNBC patients in this study demonstrated the highest NLR at recurrence (4.59) as well as the greatest increase in NLR (increase of 2.0) at recurrence.…”
Section: Nlrpredictive Of Metastasis?mentioning
confidence: 89%
“…Interestingly, we found only one study comparing NLR measurements between two different time points: pretreatment and at recurrence. The study by Iwase et al [23] found an increase in NLR by an average of 0.59 at recurrence compared to the initial measurement in a small study on patients with recurrent breast cancer. It was also reported that TNBC patients in this study demonstrated the highest NLR at recurrence (4.59) as well as the greatest increase in NLR (increase of 2.0) at recurrence.…”
Section: Nlrpredictive Of Metastasis?mentioning
confidence: 89%
“…A study in patients with post-surgery recurrent disease found a 0.59 increase in NLR (relative to its value at diagnosis) associated to recurrence (Iwase et al, 2017). On the other hand, a study that assessed NLR and the Lymphocyte to Monocyte Ratio (LMR) in 1570 patients concluded that NLR > 2 and LMR > 4.8 were associated to better DFS.…”
Section: Characteristicsmentioning
confidence: 99%
“…Increasing evidence suggests that high preoperative PNI is a predictor of better postoperative complications and patients outcomes in various types of malignancy [4][5][6][7][8][9][10]. Meanwhile, both high serum albumin level and low preoperative NLR also have been reported to be associated with better postoperative outcomes in several cancers [19][20][21][22][23][24][25][26][27]. BMI is also a well-known prognostic factor in breast cancers [28][29][30], and body weight is also associated with the patients' nutritional condition [31].…”
Section: Discussionmentioning
confidence: 99%